USING ACTIVE METHODS IN FINE ARTS LESSONS - Smaylova, Gulmari Yuldashevna (Innovative Development in Educational Activities, 2024)
The state speaks of the use of active teaching methods in teaching fine arts, the development of the student’s ability to actively learn, conducting such classes in the art of stimulation.